ANALYSIS OF SCHOOL PRINCIPALS' STRATEGIC LEADERSHIP STRATEGIES IN THE ERA OF EDUCATIONAL DIGITAL TRANSFORMATION - Evi Gusliana; Perdy Karuru; Hendrajaya Hendrajaya; Bashori Bashori; Made Ayu Anggreni (Jurnal Scientia, 2023)
The purpose of this study is to learn more about school principals' transformational leadership approaches to the digitization of education. Which aims to provide an overview of the principal's transformational leadership strategy as well as his role in empowering and utilizing digital technology in the learning process so that later students will have competencies developed through digitalization. Research is conducted using a descriptive-qualitative approach. Data sources included people, locations, and field-gathered documents. The study's findings indicate that in order for school principals to exercise transformational leadership in the field of education, they must possess the following abilities: The principal's transformational leadership strategy in influencing digitalization involves providing opportunities to develop teacher professionalism in digitalization and encouraging school change in general. Leadership plays a significant part in promoting and enhancing school quality, and it is the duty of school principals to grow their institutions through coaching and school digitalization to foster positive teamwork. School principals who increase their competence in the field of digitalization are able to make schools receive awards for their achievements in digital form, make children happier learners because it can make the learning process easier, and have positive values in the work environment, get work motivation, and have positive interpersonal relationships with digitalization. other schools, as well as having digitalization skills to develop their talents and having support from the leadership at the school.